Rethinking Interdisciplinarity across the Social Sciences and Neurosciences - Callard, Felicity; Fitzgerald, Des (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2015)
This book offers a provocative account of interdisciplinary research across the neurosciences, social sciences and humanities. Rooting itself in the authors' own experiences, the book establishes a radical agenda for collaboration across these disciplines. This book is open access under a CC-BY license.